Indonesian Capital Market Reaction Toward November, 4th 2016 Demonstration in Jakarta - Bambang Widagdo; Novita Ratna Satiti (Faculty of Economics and Business, University of Muhammadiyah Malang, 2018)
This research is a case study that aims to find out whether there is empirical evidence of Indonesia capital market reaction to one of the domestic political events, namely Demonstration 4 November 2016 by using Trading Activity Volume and Abnormal Return. The population in this research are stocks that are included in LQ45 Index in Indonesia Stock Exchange, and the data used in this research is secondary data consist of daily stock price, daily stock trading volume, and daily stock price index during the previous 30 days, one day on Time, and 30 days after the event. The statistical tool used to test the hypothesis is the t-test and the Wilcoxon Signed Rank test. The result of calculation of variance analysis shows that there is a significant difference between Stock Trading Activity Volume at the time before, during and after demo 4 November 2016. Trading Stock Activity Volume increased but not significant from process before demo November 4th to process demo November 4th, but at the demo of November 4th to the condition after the demo of November 4th has increased significantly. ANOVA test results show that there is a significant difference between Abnormal Return Shares at the time before, during and after the demo of November 4th. That Abnormal Return Shares decreased significantly from the process before the demo November 4th to process demo 4 November 4th and Abnormal Return Shares When the demo of November 4th to the condition after the demo of November 4th also experienced a significant decrease.